Digital Modernization Of Railway Interlocking Systems Using Microprocessor Shunting Signal Modules - Javokhir Juraev (Academia Open, 2026)
General Background Automation devices significantly increase transport network throughput, safety, and operational capacity. Specific Background The rapid development of digital technologies offers new opportunities for upgrading traffic control infrastructure. Knowledge Gap Traditional block-route relay architectures fail to meet modern technical requirements, yet completely replacing their existing infrastructure remains economically unfeasible. Aims This study investigates the integration and two-stage testing of NM2P-M and NM2AP-M microelectronic units designed to control station operations within legacy systems. Results Experimental laboratory evaluations and real-time station monitoring confirmed proper command exchange, accurate route setting, and functional compatibility with electromagnetic standards. Novelty The research demonstrates a step-by-step technological transformation methodology that seamlessly integrates microelectronic controllers into existing block housings without requiring significant structural modifications. Implications These findings provide a practical framework for the gradual digitalization of transport automation, accelerating fault detection and reducing maintenance costs while securing operational safety. Highlights: • The developed NM2P-M and NM2AP-M units successfully process automated commands during route setting without structural modifications. • Two-stage testing confirmed operational stability, correct hardware configuration, and electromagnetic compatibility under real-time monitoring. • Gradual technological transformation reduces maintenance costs and accelerates fault detection while preserving legacy infrastructure. Keywords: Railway Automation, Relay Infrastructure, Route Setting, Real-Time Monitoring, Functional Testing